2008
DOI: 10.1097/rhu.0b013e3181826d23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methotrexate Use in a Patient With Rheumatoid Arthritis and Multiple Sclerosis

Abstract: Rheumatoid arthritis (RA) and multiple sclerosis (MS) share similar pathophysiologic processes but coexistence of both diseases in the same patient has rarely been described. We describe the case of a 32 year old woman with rheumatoid arthritis treated with 12.5 mg of methotrexate once a week and 1 mg folic acid who developed paresthesias of her upper and lower extremities. Three years later, she acutely developed 6th nerve palsy, gait imbalance and urinary urgency and a diagnosis of multiple sclerosis was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Low-dose methotrexate has been found to diminish antigen-stimulated T-cell proliferation [2]. Two placebo-controlled double-blind studies have demonstrated that low-dose oral methotrexate (up to 7.5 mg weekly) may alter the disease course favorably in patients with progressive MS, although the long-term benefits are open to interpretation with some adverse effects [2,6]. Hydroxychloroquine/chloroquine has similar potential immunosuppressive effects including reduction of pro-inflammatory cytokines by macrophages and lymphocytes [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low-dose methotrexate has been found to diminish antigen-stimulated T-cell proliferation [2]. Two placebo-controlled double-blind studies have demonstrated that low-dose oral methotrexate (up to 7.5 mg weekly) may alter the disease course favorably in patients with progressive MS, although the long-term benefits are open to interpretation with some adverse effects [2,6]. Hydroxychloroquine/chloroquine has similar potential immunosuppressive effects including reduction of pro-inflammatory cytokines by macrophages and lymphocytes [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) and multiple sclerosis (MS) are both autoimmune diseases that share similar pathogenesis particularly of Tcell mediated process [1,2]. Nevertheless, population-based case-control studies have found that prior to the diagnosis of MS, the cases are not more likely than controls to have RA [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations